Combined laryngocele: A cause of stridor and cervical swelling - Keles, Erol; Alpay, Hayrettin Cengiz; Orhan, Israfil; Yildirim, Hanifi (Elsevier Sci Ltd, 2010)
A laryngocele is usually a cystic dilatation of the laryngeal saccule. The etiology behind its occurrence is still unclear, but congenital and acquired factors have been implicated in its development. In this study, we present a rare case of laryngocele occurring in a 72-year-old woman. During physical examination the external component of the laryngocele was seen as a swelling in the neck. The swelling became larger during Valsalva maneuver. On the endoscopic examination of the larynx, she had a bulging near the ventricular fold and the right aryepiglottic fold. Diagnosis of laryngocele was made and confirmed with physical examination, indirect laryngoscopy and magnetic resonance imaging (MRI). (C) 2009 Elsevier Ireland Ltd. All rights reserved.
Keywords: Laryngocele; Cervical swelling; Magnetic resonance imaging